Sistem Monitoring dan Kontrol Rumah Pintar Berbasis Internet Of Things Untuk Peningkatan Efisiensi Energi - Lalu Delsi Samsumar; Zaenudin Zaenudin; Ardiyallah Akbar; Emi Suryadi; Beni Ary Hidayatullah (Lembaga Pengembangan Kinerja Dosen, 2023)
The urgency of research with the theme of designing and implementing a smart home monitoring and control system based on the Internet of Things (IoT) to improve energy efficiency and quality of life is very important to carry out, in general it can be described as being able to increase energy efficiency; improve the quality of life where the system can regulate temperature, humidity and lighting to create a comfortable and healthy environment; encourage innovation; providing solutions to environmental challenges; optimizing energy availability where the smart home IoT system can regulate the use of available energy. Thus, it is very important to carry out this research to face environmental challenges and improve people's quality of life. The main objective of this research is to develop a system that can monitor and control energy use in the home efficiently, so as to improve energy efficiency and the quality of life of home residents, to overcome weaknesses and develop a holistic and effective smart home monitoring and control system. IoT based. The method used in this research is the Research and Development method, where this method is a process or steps to develop a new product or improve an existing product, which can be accounted for. The research results show that the IoT system can be designed and function well based on the results of the tests that have been carried out.